Folates dysmetabolism promotes atrial cardiomyopathy/fibrillation through a cardiac-bone marrow networking involving endothelial progenitor cell dysfunction and erythropoiesis diversion. (19th May 2022) - Sgarra, L; Caccavo, VP; Katsouras, G; Di Monaco, A; Quadrini, F; Vitulano, N; Troisi, F; Solimando, A; Cicco, S; Nacci, C; Potenza, MA; Desantis, V; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private hospital(s). Main funding source(s): dedicated cardiovascular research foud Background: Recent advances support the concept that pre-persistent Atrial Fibrillation (AF) does not explain the wholeness of embolic strokes, suggesting the recently postulated hypothesis of a broad Atrial Cardiomyopathy (AC). In contrast to its worldwide distribution and its very inclusive definition, pathogenic mechanisms underlying AC are still largely unknown. Folate cycle disorders (FCD) are a yet underrated dysmetabolism only partly explained by methylene tetrahydrofolate reductase (MTHFR)-inherited defects. On a translational basis, FCD could hinder both endothelial and circulating endothelial progenitor cell (EPCs) functioning, therefore providing one-shot explanation to both atrial stasis (increasing atrial fibrosis and generating atrial hypocontractility) and endothelial dysfunction (ED). If such cardiac-bone marrow networking would be verified, a fundamental pathogenic mechanism of AC and subsequent AF would be unraveled. Purpose: This study aims to enquire for the hypothesis that: 1) atrial fibrosis (AFib) would relate to FCD (intended as both: a)MTHFR C677T inherited mutations and b)bone-marrow function disorders, here referring to erythropoiesis diversions) and 2) AF patients would show dysfunctional EPCs. Methods: We studied 59 consecutive patients admitted to the Cardiology Unit of the General Hospital "F.Miulli", with preserved EF, subjected to AF ablation. AFib was quantified by relative % of low-voltage (<0, 5 mV) bipolar peak-to-peak points, with respect to the wholeness of the endocavitary mapping. Blood count cell was evaluated. MTHFR C677T genotypes were elucidated by RT-PCR. Folate were measured by a commercial laboratory test. EPCs isolation and characterization were performed by Ficoll-Hypaque gradient and flow cytometry analysis for cell surface antigens: CD45, CD34, CD133, VEGFR2 and KDR. EPCs functional wound healing assay was performed. Results: Baseline characteristics did not differ between Sample and Control groups (Fig. 1 – Left Table). % of Afib significantly differs between C677T MTHFR homozigosis patients (n=15) with respect to non-C677T MTHFR homozygosis patients (n=44) (Fig.1 – Right graph. - p < 0, 02). Once univariate analysis was performed, subsequent multivariate analysis highlights highest fit once merged RBC, RDW-SD and folates values were inputed: Goodness of fit was proper, modelling good (Fig.2 – superior graph. - R2=0, 39; p=0, 0001). Either RBC, RDW-SD and folates coefficient reached significance (p < 0, 0001; p < 0, 01; p < 0, 05 respectively). Number of EPCs significantly differs between AF patients and matched controls (Fig 2 – inferior graph. – p < 0, 001). Conclusions: Our findings support the hypothesis that genetically determined folates dysmetabolism (MTHFR dysfunction) promotes AFib via a complex cardiac-bone marrow networking involving circulating EPCs and unraveled by erythropoiesis diversions. Such results suggest a pathogenic role of folate cycle disorders in the AC development.